29SI AND 27AI MAS-NMR SPECTROSCOPY OF β-EUCRYPTITE (LIALSIO4): THE ENTHALPY OF SI,AL ORDERING - Phillips B.L.; Hongwu X.U.; Navrotsky A.; Heaney P.J. (My University, 2000)
By combining data from oxide melt solution calorimetry and 29Si MAS-NMR spectroscopy, the enthalpy for short-range Si.Al ordering in β-eucryptite (LiAlSiQ4) was determined for a series of samples prepared by glass annealing. Si.Al ordered β-eucryptite gives a single 29Si NMR peak for two unresolved crystallographic sites, but two distinct 27A1 resonances that differ in both chemical shift and quadrupolar coupling. Samples of β-eucryptite crystallized from glass contain additional 29Si NMR peaks, indicating significant levels of short-range Si, Al disorder. This disorder decreases exponentially with annealing time at 1173 K, from 0.55(±0.04) Al-O-Al linkages per formula unit after one hour to 0.05(±0.01) after 70.5 hours. The decrease in the concentration of A1-O-A1 linkages with annealing time correlates linearly with enthalpies of drop-solution in molten lead borate, giving an enthalpy of ΔHord = -26 ± 3 kJ/mol for the reaction: Al-O-Al + Si-O-Si → 2(Si-O-Al). Additional NMR results are presented for samples synthesized along the SiO2-Li AlSiO4 join (quartz to β-eucryptite). Solid solution samples with compositions 20 and 69 mol% quartz appear to have very few Al-O-Al linkages (<0.04 per formula unit).